Cultivo do meloeiro em sistema semi-hidroponico sob diferentes concentrações de potássio na solução nutritiva - Queiroz, Italo Sorac Rafael de (Brasil, 2016)
In northeastern Brazil, the main producing and exporting region melon, the yield exceed 40 tons per hectare. Potassium affects the concentration of sugars and nutrient relating to the maturation and the quality of the melon fruit. The semi-hydroponic system is an alternative for the growing melon, which enables efficient production and water consumption, in addition to the favorable fruit quality results. This study aimed to evaluate the growth, production and postharvest quality of melon Galia (Cucumis melo L. cultivar "Babilonia RZ F1-Hybrid"), grown in semi-hydroponic system under different levels of potassium in the nutritious solution. The experiment was carried out in greenhouse from Department of Environmental Sciences and Technology of the Universidade Federal Rural do Semi-Árido (UFERSA) from October to December 2015. The experimental design was randomized blocks, with five treatments, randomized in five blocks with six plants per plot. The effect of concentrations of potassium in the nutrient solution (50, 75, 100, 125 and 150% of the quantity of nutrients in 50% solution proposed by Furlani for melon cultivation) was analized. During the experiment variables were analyzed: plant height, stem diameter, number of leaves, fruit weight, transversal and longitudinal diameter, transverse and longitudinal inner cavity, thick peel and pulp, soluble solids, titratable acidity, pH, total sugars and fruit maturation ratio. The change in potassium concentration influenced the behavior of the growth variables, production and post-harvest. The concentration of 100% potassium caused greater increase in fruit weight, productivity and pulp thickness; with significant results for titratable acidity, total sugars and soluble solids
Concentração de potássio na solução nutritiva do meloeiro
Keywords: Cucumis melo L.; Nutrição de plantas; Cultivo sem solo; Cucumis melo L.; Nutrition plants; Soilless cultivation; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO